Plant growth-promoting bacteria for biological control of Pyricularia oryzae causing rice blast disease and biodegradation of organophosphate pesticide - Pantayak, Kultida; Bunsangiam, Sakaoduoen; Pinyakong, Onruthai; Suriyachadkul, Chanwit; Chungopast, Sirinapa; Unartngam, Jintana; Sakdapetsiri, Chatsuda (Agriculture and Natural Resources, 2026)
Importance of the work: Rice blast disease causes yield losses exceeding 50–80%, while excessive pesticide use leads to chemical accumulation and environmental concerns. Objectives: To evaluate rhizosphere bacteria multifunctional capabilities: antagonistic activity against rice blast disease, plant growth promotion and organophosphate pesticide degradation. Materials and Methods: In total, 301 bacterial isolates from the rice rhizosphere were screened for antagonistic activity against Pyricularia oryzae using the dual culture method. The antagonistic mechanisms were investigated. Selected antagonistic isolates were evaluated for plant growth promoting activities and organophosphate pesticide degradation efficiency. The isolates were identified using 16S rRNA gene sequencing. Results: Among the 301 bacterial isolates, 13 had strong antagonistic activity, with over 90% inhibition of P. oryzae mycelial growth. The antagonistic mechanisms identified were the production of volatile organic compounds, antifungal substances and cell wall-degrading enzymes (protease and cellulase). All antagonistic isolates had plant growth-promoting activity, including indole-3-acetic acid production (5.75–74.70 µg/mL with tryptophan; 2.79–15.62 µg/mL without tryptophan), phosphate solubilization, biofilm formation, siderophore production, nitrogen fixation and ammonia production. The highest mean ± SD organophosphate pesticide degradation was achieved by isolate SR4KB4.9 (48.78 ± 7.61%), followed by SR5KB5.3 (38.47 ± 4.33%) and SR4KB4.6 (33.39 ± 2.56%). Molecular identification showed these isolates were closely related to the Bacillus and Brevibacillus genera. Main finding: In total, 13 bacterial isolates had strong antagonistic mechanisms and demonstrated dual capabilities as plant growth promoters and significant degradation of organophosphate pesticide. These isolates, identified as Bacillus and Brevibacillus species, offer an integrated sustainable approach for rice cultivation